Intolerance of Uncertainty Is Associated With Increased Threat Appraisal and Negative Affect Under Ambiguity but Not Uncertainty. Issue 1 (January 2016) - Chen, Jessamine Tsan-Hsiang; Lovibond, Peter F.
Abstract: Intolerance of Uncertainty (IU) has gained increasing interest as a vulnerability factor for worry in Generalized Anxiety Disorder and other emotional disorders. We extended the procedure of Grupe and Nitschke (2011) to compare threat processing in High IU ( n = 29) and Low IU ( n = 26) participants. Participants viewed four cues: two reference cues that preceded aversive pictures on 100% or 0% of trials, and a target cue that preceded aversive pictures on 50% of trials (Uncertain condition). Participants were instructed about these probabilities in advance. In addition, we surprised participants with a second target cue that also preceded aversive pictures on 50% of trials but that had not been mentioned in the instructions (Ambiguous condition). Results provided preliminary evidence that High IU participants showed greater online threat expectancy, postexperimental covariation estimates and negative mood for the target cues compared to the reference cues. The results also suggest that among high IU individuals, ambiguity, rather than uncertainty per se, may be a particularly powerful trigger for biased threat appraisal and negative affect. Clinically, the results suggest that patients with high IU may benefit from interventions to help them calibrate the degree of risk in situations involving ambiguous threat. Highlights: We examined threat appraisal and negative affect in participants with either high or low Intolerance of Uncertainty (IU) Participants saw four cues that predicted different probabilities of an aversive picture Enhanced threat expectancy and covariation estimates were observed for the Ambiguous cue relative to the Uncertain cue High IU participants also showed enhanced negative affect for the Ambiguous cue relative to the Uncertain cue High IU is associated with biased threat processing particularly when the probability of a negative outcome is unconstrained